The spectroscopic orbit of the K‐giant binary γ Canis Minoris1. Issue 3 (1st March 2013) - Fekel, F. C.; Wiliamson, M. H.; Weber, M.; Strassmeier, K. G.; Pourbaix, D.
Abstract We have determined an improved orbit for the bright, evolved, double lined binary γ Canis Minoris. The system has an orbital period of 389.31 days and an eccentricity of 0.2586. We have revised the secondary to primary mass ratio to 0.987. The spectral types of the primary and secondary are K4 III and K1: III, respectively, and the components have a V magnitude difference of 2.2. Orbital fits to the Hipparcos astrometry are not definitive, but they suggest an orbital inclination of ∼ 66°, which produces masses of 1.88 and 1.85 M⊙ for the components. A comparison with evolutionary tracks results in an age of 1.3 Gyr. STELLA very low amplitude radial velocity residuals of the secondary indicate a period of 278 days. We interpret this as the rotation period of the secondary, detectable because of star spots rotating in and out of view. This period is nearly identical to the pseudosynchronous rotation period of the star. The primary is rotating more slowly than its pseudosynchronous rate. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)